Virtual Class Truancy in a South African Higher Education Institution: Voices from the Students - Shandu-Phetla, Thulile Pearl (Research in Social Sciences and Technology, 2025)
Academics in higher education institutions provide virtual classes as part of student support initiatives. The problem, however, is that there are persistent complaints from lecturers that students do not attend virtual classes. Using Siemens’ Connectivism as a theoretical framework, this paper presents insights on the reasons behind students’ poor attendance of virtual classes. Data were collected through a survey questionnaire consisting of open-ended questions, which was disseminated to students registered in one of the largest departments (about 130 000 student registrations) at the University of South Africa (Unisa). Following the thematic analysis of the participants’ responses, the study found that the reasons for non-attendance of classes centred around time, finances, technology issues, as well as personal preferences for independent studies. The implications for practice is a call to ODL principles of accessibility, flexibility and student support, so that academics can strategise student support for effective provision of virtual classes for the benefit of students.